Collateral damage: do gender quotas undermine party discipline?. Issue 1 (2nd January 2019) - Finke, Daniel
ABSTRACT: Quotas are the most disputed instrument to promote equal representation of women. Today, political parties in more than 90 democracies apply them. Essentially, gender quotas are a manipulation of the electoral rules. Scholars of legislative politics have created an impressive knowledge of the effect of electoral rules on political behaviour. So far, this literature remains unconnected to the literature on gender quotas. Our study contributes to closing that research gap.